STUDI KASUS KECEMASAN ANAK USIA DINI DI TK INFARUL GHOY II KELOMPOK B - Hikmawati, Lila; Winnuly, Winnuly; Rahmawati, Azizun (MAANA: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Early childhood education must be planned, stimulated and holistic. Anxiety that occurs in children cannot be ignored. This research identifies the anxiety experienced by a 5 year 6 month old girl who attends group B at Majaksingi Kindergarten, Borobudur subdistrict. There are efforts made by teachers and administrators, the reasons why students are happy/unhappy, the school's collaboration with parents, and the results of the intervention. The research approach uses qualitative research with case studies. Researchers conducted a preliminary survey, field study, literature search, and several informants. Data collection through in-depth interviews, observation methods, and documentation techniques. Analyze data in detailed descriptions of cases, collect categories, direct interpretation, form patterns, and match words. Anxiety is triggered by academic difficulties, parental demands, a history of poor health. The school provides interventions in the form of: communicating to parents, mentoring, repetition and habituation, but this has not shown maximum results.